MENINGKATKAN HASIL BELAJAR SISWA DENGAN TEKNIK ANALISIS DEKRIPTIF KUALITATIF MATA PELAJARAN BAHASA INDONESIA KELAS VIII SMP NEGERI 4 TEBING TINGGI - Bertha Elyana Gultom (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2018)
This study aims to improve student learning outcomes with qualitative descriptive analysis techniques Indonesian subjects. The research subjects were VIII grade students of SMP Negeri 4, Tebing Tinggi city. With the state of the students in the class totaling 30 students where men numbered 16 people and women numbered 14 people. From the results of research on student learning outcomes with the method of Qualitative Descriptive Analysis Technique in Class VIII of SMP Negeri 4 Tebing Tinggi has a positive impact on improving student learning outcomes. Based on the results of the questionnaire analysis the student responses can be concluded that students give a positive response to learning with a Descriptive Analysis Technique approach Qualitative. This is reinforced by interview data which states that students are interested in learning with a Qualitative Descriptive Analysis Technique approach. In addition, it can be seen from the increase in the percentage of students' mastery learning in the pre-cycle (70.17%), the first cycle 80.42%), the second cycle (92.50%).Keywords: Qualitative Descriptive Analysis Techniques, Learning Outcomes, Indonesian Language